2013
DOI: 10.3109/21691401.2013.837473
|View full text |Cite
|
Sign up to set email alerts
|

VEGF promotes cardiac stem cells differentiation into vascular endothelial cells via the PI3K/Akt signaling pathway

Abstract: Recent research suggested that cardiac stem cells (CSCs) may have the clinical application for cardiac repair. However, their characteristics and the regulatory mechanisms of their growth and differentiation have not been fully investigated. Vascular endothelial growth factor (VEGF, VEGF-A) is a major regulator of physiological and pathological angiogenesis. But the homing role of VEGF for CSCs is unclear. In this report, CSCs were isolated, purified, and expanded in vitro from rat heart. VEGF, SU5416 (VEGF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In a previous study, BM-MSCs were treated with VEGF under hypoxic conditions, and a greater proportion of BM-MSCs differentiated into endothelial cells when compared with those cultured under standard conditions (8). Xiao et al (22) demonstrated that PI3K/AKT signaling pathway served an important role in rat cardiac stem cell differentiation into endothelial cells, while Wortmannin (a PI3K/AKT signaling pathway inhibitor) was able to decrease this differentiation. Other than its role in promoting differentiation towards endothelial cells, the PI3K/AKT pathway has been shown to participate in improving neovascularization of human umbilical vein endothelial cells, and LY294002 has been demonstrated to abolish this positive effect (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, BM-MSCs were treated with VEGF under hypoxic conditions, and a greater proportion of BM-MSCs differentiated into endothelial cells when compared with those cultured under standard conditions (8). Xiao et al (22) demonstrated that PI3K/AKT signaling pathway served an important role in rat cardiac stem cell differentiation into endothelial cells, while Wortmannin (a PI3K/AKT signaling pathway inhibitor) was able to decrease this differentiation. Other than its role in promoting differentiation towards endothelial cells, the PI3K/AKT pathway has been shown to participate in improving neovascularization of human umbilical vein endothelial cells, and LY294002 has been demonstrated to abolish this positive effect (32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, qPCR was used to measure the gene expression of VEGF, which is the most important angiogenesis-associated cytokine (22). Following appropriate treatment for 7 days, 1×10 6 cells were collected from each group, and total RNA was prepared from the cells using TRIzol reagent (Invitrogen; Thermo Fisher Scientific, Inc.) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“… 114 Preclinical animal studies demonstrated that VEGF-A 165 gene therapy resulted in the induction of angiogenesis, arteriogenesis, and vasculogenesis, 92 , 93 recovery of ventricular function during ischaemia, reduction in apoptosis of the infarcted area. 94 VEGF also plays a role in the recruitment and homing of cardiac and endothelial progenitor cells 115 and maintenance of physiological homeostasis in the heart. 116 Translational studies in large animal models confirmed some of the beneficial effects of VEGF, either by itself or in combination with other angiogeneic factors (e.g.…”
Section: Therapeutic Genes For Gene Therapy For Cvdmentioning
confidence: 99%
“…VEGF binding stimulated proliferation and decreased apoptosis of endothelial cells, leading to the increased efficiency of ischemic hindlimb treatment. In addition, VEGF prevents apoptosis through phosphatidylinositol (PI)-3-kinase Akt pathway or through the stimulation of antiapoptosis Bcl-2 and A1 factors production in endothelial cells (Karar and Maity, 2011;Xiao et al, 2014). PI-3-kinase Akt pathway activates vascular growth factors such as eNOS and HIF-1α.…”
Section: Discussionmentioning
confidence: 99%